Hubungan antara Perilaku Penjamah Makanan dengan Penerapan Higiene Sanitasi Makanan pada Rumah Makan di Palembang - Deswitary Handhayani; Kamsul, Kamsul; Saputra, Fider (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Mamuju, 2026)
Food hygiene and sanitation is an important aspect in maintaining food safety and preventing foodborne illnesses. Restaurants as places for food processing and serving have a high potential for contamination if food handlers do not implement good hygiene and sanitation practices. The knowledge, attitudes, and actions of food handlers are influential factors in maintaining the quality of sanitation during the processing process. This study aims to determine the relationship between the knowledge, attitudes, and actions of handlers and food sanitation hygiene in restaurants in the working area of the Kertapati Health Center, Palembang City in 2025. This study uses an analytical study design with a cross-sectional approach. The sample consisted of food handlers who worked at restaurants registered in the Kertapati Health Center area, with purposive sampling techniques. Data collection was carried out through questionnaires and observations using a food hygiene checklist sheet. Statistical analysis uses chi-square test. The results showed that the knowledge variable did not have a significant relationship with food hygiene (p-value = 0.0598), indicating that the level of knowledge of the handlers has not been fully reflected in real practice. In contrast, the attitude and action variables showed a significant relationship with food hygiene (p-value < 0.05). Food handlers with a positive attitude and actions that comply with standards tend to implement better sanitary hygiene practices. These findings confirm that improving attitudes and actions is an important aspect in efforts to improve food hygiene and sanitation in restaurants. It is recommended that the management and health center conduct routine coaching, training, and periodic monitoring to improve the optimal implementation of food hygiene